2007
DOI: 10.1086/522160
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Preventive Treatment against Malaria in Infants in Gabon—A Randomized, Double‐Blind, Placebo‐Controlled Trial

Abstract: ClinicalTrials.gov identifier: NCT00167843.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…At the age of 3, 9 and 15 months we recorded the weight and height of children who were followed up in a longitudinal study to assess the efficacy (regarding the outcomes malaria and anaemia) and safety of intermittent presumptive treatment in infants through sulphadoxine pyrimethamine administered at the age of 3, 9 and 15 months that had started in December 2002 (16)(17)(18) . Written consent was obtained from all primary caregivers of all study children enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…At the age of 3, 9 and 15 months we recorded the weight and height of children who were followed up in a longitudinal study to assess the efficacy (regarding the outcomes malaria and anaemia) and safety of intermittent presumptive treatment in infants through sulphadoxine pyrimethamine administered at the age of 3, 9 and 15 months that had started in December 2002 (16)(17)(18) . Written consent was obtained from all primary caregivers of all study children enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting "IPTi Consortium" ( www.ipti-malaria.org ), has supported efficacy trials of IPTi in five countries, and together with other groups has generated information on safety, efficacy, potential interactions with the Expanded Program on Immunization (EPI) vaccines, resistance, acceptability, immunology, cost, and cost-effectiveness. [7][8][9][10][11][12][13][14][15][16] A recent independent review of IPTi concluded that "the evidence makes IPTi with sulphadoxine-pyrimethamine a promising public health strategy." 17 Efficacy is defined as the impact achieved by interventions when given in research settings.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent preventive treatment for malaria in infants (IPTi) is a promising new intervention consisting of the administration of a treatment dose of sulfadoxine/pyrimethamine (SP) at the time of routine vaccinations in the first year of life. 3 A pooled analysis 4 of six randomised controlled trials (RCT) of IPTi using SP (IPTi-SP) [5][6][7][8][9][10] suggested that the intervention can reduce the incidence of clinical malaria in the first year of life by 30%. If such an effect can be achieved by delivering an available and affordable antimalarial treatment at the time of routine contacts with the health system, IPTi-SP may become a useful component of antimalarial strategies in some settings.…”
Section: Introductionmentioning
confidence: 99%